The ABSI is dead, long live the ABSI - reliable prediction of survival in burns with a modified Abbreviated Burn Severity Index. Issue 6 (September 2020) - Bartels, Pia; Thamm, Oliver C.; Elrod, Julia; Fuchs, Paul; Reinshagen, Konrad; German Burn Registry,; Koenigs, Ingo
Highlights: The Abbreviated Burn Severity Index (ABSI) was applied to a cohort of 14, 984 patients. Mortality was overestimated considerably, mainly in severe burns. The ABSI does not reflect modern treatment anymore. A modified and easy-to use ABSI was developed excluding sex and adjusting for age. The modified ABSI re-establishes accuracy in predicting mortality in burns. Abstract: Objectives: The Abbreviated Burn Severity Index (ABSI) is a widely used and simple score to predict mortality after burn injuries. On the one hand, significant improvements in intensive care management and surgical treatment result in an increased survival rate. On the other hand, the aging population might lead to an increased injury-related mortality rate. Therefore, the question arises whether the ABSI still accurately predicts survival. Methods: Data of 14, 984 patients from the German Burn Registry from 2015 to 2018 were analyzed to re-evaluate the variables included in the ABSI, identify discrepancies between the predicted age-related probability of survival and the actual survival rate. Descriptive statistics, univariate analysis and binary logistic regression were used to test the variable impact and to establish a modified score. Results: The original ABSI does not accurately predict the survival in the present cohort. In particular, univariate analysis identified age, total body surface area burned, full thickness burn and inhalation injury as significant impactors on survival. Moreover, sex could not be confirmed as significant and was, therefore, excluded from the modified score. The assumption of a linear relation between age and mortality was not correct. We developed a new age scale representing the actual existing relationship. The resulting modified score was significantly more accurate in predicting the probability of survival for all burn score categories. Conclusion: The ABSI does not accurately predict probability of survival. Mortality is overestimated in severely burned patients. A modified version was developed that was significantly more accurate in predicting the probability of survival in this cohort.